Carotid artery stenting without post-dilation - Spacek, Miloslav; Zimolova, Petra; Veselka, Josef (Journal of interventional cardiology, 2012)
INTRODUCTION: The aim of this study is to report the feasibility, safety, and 1-year restenosis rate of carotid artery stenting (CAS) without post-dilation. METHODS: Between April 2006 and November 2009, 254 consecutive patients (68.7 ± 8.5 years old, 31% symptomatic) underwent 308 CAS procedures with the intention of avoiding post-dilation (eligibility criteria were stenosis of less than 30% after stent placement with no overt signs of calcification). Comparison and analysis of mid-term clinical outcomes and restenosis rates of CAS with or without post-dilation was performed retrospectively. RESULTS: Overall, 27 patients (study group) were eligible for treatment without post-dilation. No significant difference in adverse events was found between the study and control group. In the study group, 2 transient ischemic attacks (7.4%) occurred immediately after the procedure and no other neurological complications were reported during the 30-day, 6-month, and 1-year follow-ups (3 patients died from causes unrelated to the procedure). Two asymptomatic restenosis cases were diagnosed in the study group within the first 12-months after the procedure compared to 16 significant restenosis cases diagnosed in the control group (7.4% vs 5.7%, NS). All of them were successfully treated with repeated intervention. CONCLUSION: We suggest that CAS without post-dilation is feasible and probably safe with a low rate of cerebrovascular events and restenosis in a selected group of patients. We also suggest that CAS with postdeployment stenosis of less than 20% and without overt signs of severe calcification might be performed without post-dilation.
Keywords: katetrizace; recidiva; stenty; Catheterization; Humans; Prosthesis Implantation; lidé středního věku; tranzitorní ischemická ataka; výběr pacientů; Patient Selection; Female; implantace protézy; lidé; Ischemic Attack, Transient; Stents; Carotid Stenosis; ženské pohlaví; Male; Middle Aged; Retrospective Studies; stenóza arteria carotis; Recurrence; retrospektivní studie; mužské pohlaví